THE ROLE OF ARTIFICIAL INTELLIGENCE IN SHAPING THE FUTURE OF OLYMPISM: AN ANALYSIS OF THE ROLE OF NATIONAL OLYMPIC COMMITTEES - Pereira Coelho, Eduardo (Πανεπιστήμιο Πελοποννήσου, 2025)
The Olympic Movement is a humanistic movement that promotes the holistic development of the individual. In contemporary society, Artificial Intelligence (AI) emerges as a technology with the potential to influence and transform all areas of human life. At the intersection of these two phenomena are the National Olympic Committees (NOCs), which play a fundamental role in integrating AI into the Olympic Movement. This study explores the transformative potential of AI in the Olympic context and examines the role of NOCs in its implementation, based on the perceptions and expectations of NOCs representatives and experts. Through a mixed method approach, a semi-structured survey was conducted (n=33) with NOCs about AI adoption, perceptions of its impact, benefits, and ethical considerations. Additionally, semi-structured interviews were conducted with experts and stakeholders in the Olympic Movement (n=11) to evaluate the challenges and opportunities associated with AI implementation in the Olympic context. The findings highlighted that NOCs, as links between the International Olympic Committee (IOC) and local communities, perceive AI as a tool to optimize athlete performance, improve governance, and enhance spectator engagement. However, barriers such as resource limitations, ethical concerns, and cultural resistance were noted. The study concludes that AI holds transformative potential in the Olympic context. As pivotal mediators between the IOC and local communities, NOCs must strategically address the mentioned barriers to fully leverage AI’s benefits for the advancement of Olympism.
Keywords: Τεχνητή νοημοσύνη - Ηθικές απόψεις; Ολυμπιακό κίνημα; Ολυμπισμός; Artificial intelligence - Moral and ethical aspects; Olympic movement; Olympism; Artificial Intelligence; Olympism; Humanism; National olympic committees; Ethics; Future